Morphological and optical investigation of 2D material-based ternary nanocomposite: Bi2O3/MgO/GO synthesized by a co-precipitation technique. Issue 51 (17th November 2022) - Urooj, Ashwa; Rani, Malika; Shah, Aqeel Ahmad; Aslam, Samina; Siddiqui, Rabia; Siddiqa, Aisha; Neffati, R.; Chandio, Ali Dad
Abstract : A ternary oxide nanocomposite based on Bi2 O3 /MgO/GO was prepared using a co-precipitation method taking into consideration of preparing the material for photoconductive device applications. Abstract : A ternary oxide nanocomposite based on Bi2 O3 /MgO/GO was prepared using a co-precipitation method for photoconductive device applications. The structure and morphology of the as-prepared nanocomposite were characterized analytically using X-ray diffraction (XRD), scanning electron microscopy (SEM), electron dispersive spectroscopy (EDS) techniques, and optical characterization was made using Fourier-transform infrared (FTIR) spectroscopy, photoluminescence (PL), and UV-vis spectroscopy techniques. The heterostructure of the crystal with a crystallite size of 28.064 nm and the purity of the phase are depicted by XRD patterns. Scanning electron microscopy revealed its morphology showing an average grain size of 0.27 μm, and the purity of the nanocomposite was confirmed by EDS, which showed the presence of Mg, Bi, C, and O. The band gap of the Bi2 O3 /MgO/GO nanocomposite was 4.02 eV by PL comparable with 5.718 eV by UV-vis spectroscopy, which evidenced that the material may have potential applications in far UVC emissive devices. The zeta potential observed was 48.0 mV, indicating the stability of the ternary nanocomposite.